Policy effect estimation and visualization in linear panel event-study designs: Introducing the xtevent package - Simon Freyaldenhoven; Christian Bailey Hansen; Jorge Pérez Pérez; Jesse M. Shapiro; Constantino Carreto (Banco de México, 2024)
Linear panel models and the "event-study plots" that often accompany them are popular tools for learning about policy effects. In this paper, we introduce the "xtevent" package for Stata, which enables the construction of event-study plots following the suggestions in Freyaldenhoven et al. (forthcoming). The package implements various procedures to estimate the policy effects that underlie the plots, and allows for non-binary policy variables and estimation adjusting for pre-event trends.
Keywords: C23; C87; C53; 330; Xtevent; linear panel data models; two-way fixed effects regression; pre-trends; event study